2023
DOI: 10.1111/add.16130
|View full text |Cite
|
Sign up to set email alerts
|

Directional associations between cannabis use and depression from late adolescence to young adulthood: the role of adverse childhood experiences

Abstract: Background and aims Although the co‐occurrence of cannabis and depression is well established, less is known about the temporal sequence of cannabis use and depression. The present study had three main aims: to test a symptom‐driven pathway in which depression may drive increases in cannabis use, to test a substance‐induced pathway in which cannabis use may drive increases in depression and to assess a shared vulnerability model assessing associations between individuals who have (and have not) experienced adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…These findings are consistent with prior studies linking marijuana use to mental health problems in older adults 15,21,43 . Although some individuals with mood disorders may be attempting to self‐medicate their symptoms with marijuana, there is evidence from longitudinal studies of younger people that marijuana use, especially frequent and/or heavy use, increases the likelihood of these symptoms 44–48 . Similarly, reductions in marijuana use may result in decreased depression scores 49,50 although this work needs to be replicated in older adults.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These findings are consistent with prior studies linking marijuana use to mental health problems in older adults 15,21,43 . Although some individuals with mood disorders may be attempting to self‐medicate their symptoms with marijuana, there is evidence from longitudinal studies of younger people that marijuana use, especially frequent and/or heavy use, increases the likelihood of these symptoms 44–48 . Similarly, reductions in marijuana use may result in decreased depression scores 49,50 although this work needs to be replicated in older adults.…”
Section: Discussionsupporting
confidence: 84%
“…15,21,43 Although some individuals with mood disorders may be attempting to self-medicate their symptoms with marijuana, there is evidence from longitudinal studies of younger people that marijuana use, especially frequent and/or heavy use, increases the likelihood of these symptoms. [44][45][46][47][48] Similarly, reductions in marijuana use may result in decreased depression scores 49,50 although this work needs to be replicated in older adults. Research conducted in younger people indicates that the link between marijuana use and psychiatric symptoms may be related to reduced dopamine synthesis capacity in individuals who use marijuana.…”
Section: Discussionmentioning
confidence: 98%
“…Among these studies, 22 identified a significant temporal association between baseline cannabis use and subsequent depression. Cannabis use was a significant predictor of adulthood depression across 12 sample sets following adolescents ( 20 , 34 , 42 , 59 , 60 , 66 , 70 , 74 , 78 , 82 , 84 , 89 ). In a sample of LGB and heterosexual adolescents, London-Nadeau and colleagues observed that cannabis use at age 13 predicted depression symptoms at ages 15 and 17 among LGB participants only ( 70 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, a bidirectional relationship was also identified among LGB adolescents, where baseline depressive scores predicted subsequent cannabis use. In one study that tracked a cohort of Australian young adults from birth, and after controlling for covariates, individuals who used cannabis at least once a week were more likely to report depressive symptoms than those who never used cannabis or those who used cannabis less than weekly ( 42 ). Furthermore, among young adults who used cannabis at least weekly, the risk of reporting depressive symptoms was greater among those who initiated cannabis use before the age of 15.…”
Section: Resultsmentioning
confidence: 99%